2011
DOI: 10.1108/03068291111131409
|View full text |Cite
|
Sign up to set email alerts
|

Gender inequality and the spread of HIV‐AIDS in India

Abstract: Purpose -The purpose of the paper is to analyze the low status of women as being a major contributor for the observed gender inequality in the spread of HIV/AIDS in India. indicate men are more likely to be infected with HIV/AIDS, the rate of decline is higher for men compared to women in India. We explore several plausible explanations for such observed inequality in the spread of HIV/AIDS across gender. In particular, a potentially important factor -the low status of women in society is attributable as an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Many women in South India, particularly poor rural women, are unaware of the risk of HIV transmission from their husbands [6,15,26]. Furthermore, cultural and historical expectations of a wife's subordination to her husband mean that women often have little control over marital sexual activity or safe-sex practices [12,26].…”
Section: Women In India Living An Hiv: the Pieces Of A Stigma Riddledmentioning
confidence: 99%
See 4 more Smart Citations
“…Many women in South India, particularly poor rural women, are unaware of the risk of HIV transmission from their husbands [6,15,26]. Furthermore, cultural and historical expectations of a wife's subordination to her husband mean that women often have little control over marital sexual activity or safe-sex practices [12,26].…”
Section: Women In India Living An Hiv: the Pieces Of A Stigma Riddledmentioning
confidence: 99%
“…Furthermore, cultural and historical expectations of a wife's subordination to her husband mean that women often have little control over marital sexual activity or safe-sex practices [12,26]. It is reported that HIV tests are often performed without the woman's consent, with results communicated to her husband's family, so, even after diagnosis the woman may not be advised of her condition or receive treatment [1,6,15]. Family resources are typically prioritised toward the husband's care by the wife and the husband's family [26].…”
Section: Women In India Living An Hiv: the Pieces Of A Stigma Riddledmentioning
confidence: 99%
See 3 more Smart Citations